Kinematic performance analysis of a 2RPU-RPUR parallel mechanism without parasitic motion - CHE Linxian; HUANG Xin; PENG Siyang; WANG Yuanze; LAN Jun (Jixie chuandong)
ObjectiveA novel semi-symmetrical 2RPU-RPUR parallel robot mechanism with one translational and two rotational degrees of freedom and without parasitic motion was presented to orientate cutting requirements, and it can be used as a parallel model of the 5-degree-of-freedom (5-DOF) machining robot.MethodsFirstly, the screw theory was employed to analyze the degree-of-freedom of the parallel mechanism, and the position analysis model of the mechanism was established based on the closed-loop vector method. The analytic equations for forward and inverse position solutions were presented. Then the results show that the mechanism structure was characterized by partial decoupling. Based on this feature, the Shengjin’s formula was utilized to solve the displacement equation along the Z-direction of the platform, and the forward displacement solutions with symbolic and analytic expressions were obtained. Secondly, the analytic expressions of forward and inverse solutions to the velocity and acceleration were also derived. The forward kinematic solutions of the parallel mechanism were simulated and verified by providing the actuating inputs of the mechanism. Thirdly, the geometric constraints were utilized to analyze the reachable workspace of the mechanism. On this basis, the definitions and calculating methods of evaluation indices were proposed for the local transmission capacity, good transmission orientation workspace, and regular workspace, etc. Finally, a 5-DOF hybrid machining robot with the novel parallel mechanism as the core module was designed, and its strength and stiffness was analyzed using the Ansys software.ResultsThe research results indicate that the 2RPU-RPUR mechanism can serve as a parallel spindle head which is jointed in series with two prismatic pairs to meet the 5-axis machining requirements.